Homophobia, Fundamentalism, and Canadian Tolerance: Enabling Gay Games III in Vancouver - Davidson, Judy (International Journal of Canadian Studies / Revue internationale d’études canadiennes, 2007)
Gay Games III were held in Vancouver in August 1990. This paper analyzes the effects of three different moments of homophobic backlash faced by organizers of that event. While quiet institutional homophobia might have been tolerated, public representations of blatant homophobia could be mobilized by the organizers of Gay Games IIII to their advantage. The effects of a hateful campaign paradoxically functioned as an interesting condition of possibility for Gay Games' credibility. I then suggest that the limitations of these liberal strategies were shown up by the fractures within local lesbian and gay communities, demonstrating the weaknesses of accepting tolerance as a limit to the possible.